Facile Density Measurement Method for High-Concentration Sulfate Determination. (1st December 2022) - Oreiro, Sara Noriega; Berdiyeva, Perizat; Bentien, Anders
Abstract : In this study, a fast, facile and high accuracy method for high concentration sulfate determination is presented. The method is based on precipitation of sulfate ions with barium ions. The sulfate amount is quantified by measurement of the density of the barium and sulfate ion solutions before mixing, and the density of the supernatant after mixing. A calibration curve for sulfate concentration between 2.5 and 5.5 M in vanadium electrolyte was performed, obtaining a precision better than 0.7%, in agreement with a propagation-of-error analysis. Accuracy is determined by one-point calibration against a sample with known sulfate concentration and is at best the same as the precision. Within the precision of the method, no systematic effect of the presence of other ions/interferents (vanadium, phosphate) on the sulfate determination is observed.